Photo- and radiation-chemical formation and electrophilic and electron transfer reactivities of enolether radical cations in aqueous solution - Bernhard, Klaus; Geimer, Judith; Canle-Lopez, Moises; Reynisson, Johannes; Beckert, Dieter; Gleiter, Rolf; Steenken, Steen (Chemistry - a European journal, 2001)
In aqueous solution, enolether radical cations (EE.+) were generated by photoionization (?≤222 nm) or by electron transfer to radiation-chemically produced oxidizing radicals. Like other radical cations, the EE.+ exhibit electrophilic reactivity with respect to nucleophiles such as water or phosphate as well as electron transfer reactivity, for example, towards one-electron reductants such as phenols, amines, vitamins C and E, and guanine nucleosides. The reactivity of these electron donors with the radical cation of cis-1,2-dimethoxyethene.+ (DME.+) can be described by the Marcus equation with the reorganization energy ?=16.5 kcal?mol?1. By equilibrating DME.+ with the redox standard 1,2,4-trimethoxybenzene, the reduction potential of DME.+ is determined to be 1.08±0.02 V/NHE. The oxidizing power of the radical cation of 2,3-dihydrofuran, which can be considered a model for the enolether formed on strand breakage of DNA, is estimated to be in the range 1.27?1.44 V/NHE.
Gesehen am 22.10.2020